Positive determinants word-of-mouth of supermarket consumer in the COVID-19 pandemic era - Sri Vandayuli Riorini; Genesis Sembiring Depari (Jurnal Manajemen dan Pemasaran Jasa, 2021)
This research, which was conducted in the era of the COVID-19 pandemic, aims to analyze the influence of the dimensions of service quality, competitive prices, customer satisfaction toward the positive word-of-mouth of Supermarket customers. Questionnaires were distributed to 350 respondents as samples using the non-probability sampling method and purposive sampling technique. Meanwhile, Structural Equation Modeling (SEM) is used to analyze the data. The results of the study indicate that Reliability, Assurance, Tangibles, Empathy, Responsiveness, Competitive Price have positive and significant effects onCustomer Satisfaction, which in turn would have a positive impact on positive word-of-mouth. Of all dimensions of service quality, the most powerful factor influencing consumer satisfaction shopping in supermarkets is reliability, and the one that gives consumers the most important feeling in providing quality services is Responsiveness. For further research, it is recommended to expand the scope of research in various types of businesses, not only in supermarkets.